Review Dampak dan Tantangan dalam Penerapan HR Analytics untuk Meningkatkan Performa Perusahaan - Amin Kiswantoro; Dwiyono Rudi Susanto; Meiana Maulida Hikmawati; Nur Rohman; Gagih Pradini (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
HR analytics is a methodology that allows someone to carry out analysis by looking at patterns from available data so that they can drive change and provide more value to the company. The purpose of this research is to determine the results of the impacts and challenges in implementing HR Analytics to improve company performance. The method used is selected data obtained via Google Scholar which is entered into a table in CSV format. Furthermore, the database was used as a basis for conducting theoretical studies and literature reviews which were then analyzed using qualitative descriptive analysis methods. The results of the research found that HR analytics has a positive impact on organizational or company performance. Applying HR analytics and evidence-based decision making can improve organizational performance because company managers succeed in making the right decisions according to conditions in the field, improving organizational performance in recruiting employees according to job positions. Not all companies are ready to implement HR analytics, because it takes time to carry out the process and to implement it, not as fast as the theory proposed by academics.